2019
DOI: 10.1016/j.ajo.2018.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Specialist Detection of Optical Coherence Tomography Suspicious Rim Tissue in Glaucoma and Glaucoma Suspect Eyes

Abstract: Purpose: To assess glaucoma specialists' detection of optic nerve head (ONH) rim tissue that is thin by optical coherence tomography (OCT) criteria. Design: Reliability analysisMethods: 5 clinicians marked the disc margin (DM) and rim margin (RM) on stereo-photos of 151 glaucoma or glaucoma suspect eyes obtained within 3 months of OCT imaging. The photo and OCT infrared image for each eye were colocalized and regionalized into twelve sectors relative to the axis between Bruch's membrane opening (BMO) centroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…[20][21][22] Frequently, the innermost extension of Bruch's membrane beyond the border tissues is invisible to the clinician, making disc margin-based ''disc size'' estimates inaccurate. [20][21][22] FIGURE 1. OCT optic nerve head (ONH) and neural canal landmarks from the left eye of study subject FDA 287 shown in right eye orientation.…”
mentioning
confidence: 99%
“…[20][21][22] Frequently, the innermost extension of Bruch's membrane beyond the border tissues is invisible to the clinician, making disc margin-based ''disc size'' estimates inaccurate. [20][21][22] FIGURE 1. OCT optic nerve head (ONH) and neural canal landmarks from the left eye of study subject FDA 287 shown in right eye orientation.…”
mentioning
confidence: 99%